Digitalisasi Bank Sampah “Sugema” Sebagai Pusat Edukasi Pengelolaan Sampah di Kelurahan Kotabaru Kecamatan Cibeureum Kota Tasikmalaya - Setiadi, Pidi Muhammad; Respati, Resa; Alia, Dwi; Lidinillah, Dindin Abdul Muiz; Gandana, Gilar; Nugraha, Dadan (IPI Press, 2024)
In 2020, Tasikmalaya City as an area that contributes 106 thousand tons of waste per year, if calculated per person, it will produce 0.44 kg of waste per day. In response to this, residents in the Perum Kotabaru Kencana RW 018 Kelurahan Kotabaru, Cibeureum District, Tasikmalaya City established the